PENYULUHAN TEKNIK RELAKSASI OTOT PROGRESIF UNTUK MENURUNKAN KADAR GULA DARAH PADA PASIEN DIABETES MELLITUS TIPE 2 DI RUMAH SAKIT GRANDMED - Sari Desi Esta Ulina Sitepu; Tati Murni Karo-karo; Pratiwi Christa Simarmata; Amriani Eva Perawati Silalahi; Kardina Hayati; Selamat Tuahta Sipayung (JURNAL PENGMAS KESTRA (JPK), 2021)
The prevalence of diabetes that occurred in 2015 was 9.3% and is expected to continue to increase every year. Type 2 diabetes mellitus occurs due to insulin resistance, namely glucose that fails to enter the body, usually occurs at the age of over 30 years. One form of therapy that can be done is progressive muscle relaxation. The purpose of this community service is to find out the benefits of progressive muscle relaxation techniques on reducing blood sugar levels in patients with type 2 diabetes mellitus at Grandmed Lubuk Pakam Hospital. The method used in this community service is a quasi-experimental using observation sheets. The application of muscle relaxation techniques was carried out on 10 patients with type 2 diabetes mellitus. The community service procedure started from an explanation of progressive muscle relaxation techniques and procedures, implementation and observations (observations), then the results were recorded in the observation sheet. The application of progressive muscle relaxation techniques in patients with type 2 diabetes mellitus accompanied by insulin injection has been shown to reduce blood sugar levels. The application of progressive muscle relaxation techniques can be used as an intervention in lowering blood sugar levels in patients with type 2 diabetes mellitus.